The nature of interaction between Israeli entrepreneurs and investment capital available within and from outside Israel - Friedman, Avishai (Auckland University of Technology, 2008)
Israel is a small country that has rapidly become a global leader in production of high-tech goods. Supporting this industry is strong investment and high levels of entrepreneurship. Some scholars suggest a close similarity between the Israeli Venture Capital industry and that of Silicon Valley. To validate that claim I have closely replicated a network model developed for entrepreneur-venture capital interactions in Silicon Valley and applied it to Israel. This has been achieved through mapping the linkages with a 3D network modelling software (Pajek) between biotech firms created since 2000 and other players in the Israeli market such as venture capital funds, universities and government institutions. Information gathered on the entrepreneurs responsible for the biotech firms creation suggests that the majority are either professors at research institutes or hold a doctorate degree, suggesting strong linkages between the entrepreneurs and their research institutes. Many firms are also found to employ professional management teams. The matrix of inter-connections and supporting institutions suggests that biotech research institutions have a strong focus on fostering commercialization of new technologies. There is also abundant support for high-tech and venture capital from the Israeli government, which is a point of difference between Israel and Silicon Valley. Taken together the strong presence of institutions and of government support may explain,at least in part, the attractiveness of Israel for investors despite the country’s precarious and uncertain condition as one of the global war and conflict hot spots.
Keywords: Information technology; Political economy; Entrepreneurial literature; Classical economic literature; Business environment; Israeli business history